2020
DOI: 10.1111/odi.13288
|View full text |Cite
|
Sign up to set email alerts
|

Histological characteristics of early‐stage oral tongue cancer in young versus older patients: A multicenter matched‐pair analysis

Abstract: Little is known about the histopathological characteristics that may differentiate early oral tongue cancer (OTSCC) between young and older patients. From a total of 311 cases diagnosed with clinically early‐stage OTSCC at 6 institutions, only 42 patients were young patients were aged ≤45 years. For comparison, 42 patients >60 years old were matched for center of management, clinical stage and gender. We compared epithelial and stromal histopathologic parameters between the two groups. Most of the parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
2
7
1
Order By: Relevance
“…In young adults, the role of prognostic factors such as genetic or histopathological alterations has been studied 33‐35 . In this regard, the discussion has focused on the role of unknown risk and prognostic factors in young patients with OTSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In young adults, the role of prognostic factors such as genetic or histopathological alterations has been studied 33‐35 . In this regard, the discussion has focused on the role of unknown risk and prognostic factors in young patients with OTSCC.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of OSCC has increased in many countries, especially in younger individuals, but whether young and old patients with OSCC have a different prognosis is controversial [2]. Recent studies have revealed no significant differences in tumor stage or grade in the comparisons of the characteristics of OSCC in young and old patients [3][4][5]. Therefore, the discovery of factors that facilitate OSCC prognosis is one of the key challenges that we need to overcome.…”
Section: Introductionmentioning
confidence: 99%
“…This result supports the previous study that compared the clinicopathology of early stage OTSCC between young and elderly adults. [ 16 ]…”
Section: Resultsmentioning
confidence: 99%